THE TRAINING OF TEACHERS IN THE PERSPECTIVE OF EDUCOMMUNICATION - Santos, Isabel Pereira dos (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
This paper presents the convergences between the foundations of emancipatory education and the foundations of Educommunication. It shows the relevance of the application of both aspects in the teacher training process and presents the areas of Educommunication as possibilities of action in the universe of educommunication practices.